Ecoanalytics as A New Area of The Analysis of Environmental Conditions at An Enterprise - Yu. G. Chernysheva (International Business and Accounting Research Journal, 2020)
This article studies the aspects of environmental safety issues. It characterizes the methods of assessment of environmental condition in Russia and abroad. The nature of ecological audit and its purpose are considered. The article highlights the problems of regional programs in Russia related to the improvement of the environmental condition. The essence of the analysis of the ecological state of the organization in Russia is revealed. The peculiarities of the appearance of a new analytical direction of eco-analysis within the organization have been identified and described.